Effect of the change of the ancillary carboxylate bridging ligand on the SMM and luminescence properties of a series of carboxylate-diphenoxido triply bridged dinuclear ZnLn and tetranuclear Zn2Ln2 complexes (Ln = Dy, Er). Issue 1 (5th December 2018) - Echenique-Errandonea, E.; Zabala-Lekuona, A.; Cepeda, J.; Rodríguez-Diéguez, A.; Seco, J. M.; Oyarzabal, I.; Colacio, E.
Abstract : SMM behavior and intense photoluminescence are reported for eleven dinuclear and tetranuclear compounds. Abstract : Eleven new dinuclear and tetranuclear compounds of general formulae [Zn(μ-L)(μ-X)Ln(NO3 )2 ]·nS, [Zn2 Dy2 (μ3 -L′)2 (μ-sal)2 (NO3 )(CH3 OH)](NO3 )·5CH3 OH and [Zn2 Er2 (μ3 -L′)2 (μ-sal)2 (CH3 OH)2 ](NO3 )2 ·4CH3 OH (X = benzoate, anthracenate, diclofenac, salicylate, 2, 6-dihydroxybenzoate; Ln = Dy, Er; S = water, acetonitrile, methanol) were prepared from the N, N ′-dimethyl- N, N ′-bis(2-hydroxy-3-formyl-5-bromobenzyl)ethylenediamine compartmental ligand (H2 L). Complexes1–6 and9–11 consist of diphenoxido-carboxylate triply bridged compounds, which differ mainly in the carboxylate bridging ligand. It should be noted that the acidic character of the salicylic acid promotes, in the presence of methanol, the methoxylation of the H2 L ligand thereby yielding a hemiacetal H3 L′, which is able to connect the Ln(iii ) ions of two ZnLn dinuclear units forming the Zn2 Ln2 tetranuclear complexes7 and8 . All compounds display SMM behaviour in the presence of an external field with effective energy barriers ( U eff ) as high as 61 K. Magneto-structural data for these complexes reveal that their SMM behaviour is not only significantly affected by the type of Ln(iii ) ion but also by the carboxylate bridging ligand connecting the Zn(ii ) and Ln(iii ) ions. Photoluminescence properties have also been accomplished, showing that the ligands are able to sensitize lanthanide centred emissions in the visible and near-infrared regions with variable capacity. Moreover, the analysis of the luminescence decay curves reveals emission lifetimes in the range of few microsecond or hundreds of nanoseconds for Dy(iii )-based or Er(iii )-based luminophores, respectively.